Characterization of Purified Collagen from Marine Squid Uroteuthis Duvauceli: Life Sciences-Biotechnology for Prospective Medical Science - Jency George; Dr. Manjusha W. A. (International Journal of Life Science and Pharma Research, 2022)
Collagen is the essential and most abundant structural protein found in the animal kingdom, involving almost 25-30% of the entire body protein content. It is normally found in fibrous tissues, for example, skin, tendons, ligaments, skin, corneas, ligament, bones, veins, teeth, and so on. The skin of the squid is rich in collagen and is an excellent source of raw materials that can be used for the development of collagen products. As such, the use of Uroteuthis duvauceli skin is an alternative source of collagen may be an effective way to obtain high-value-added products. In this study, - the isolated Type 1 collagen was found in Uroteuthis duvauceli (skin and muscle ). Additionally, the characterization of the Type 1 collagen from Uroteuthis duvauceli (skin and muscle ) was examined through various techniques such as SEM, FTIR, XRD, TGA. The skin and muscle showed the typical SDS-PAGE pattern of type I collagen with two different α bands, α1 and α2 and also contains β and γ chains. The fibrillar structures of collagen samples were observed by SEM. FTIR investigation showed the existence of helical arrangements of the type 1 collagen from skin and muscle. UV spectrum of Type1 collagen from Uroteuthis duvauceli skin and muscle has a maximum absorption peak near 230 nm and a minor absorption peak near 280 nm. In XRD, type1 collagen from Uroteuthis duvauceli skin and muscle one wide peak was obtained following with characteristic diffraction peaks of collagen. The results showed that type 1 collagen from skin and muscle had slight differences in molecular weight, amino acid composition, morphological structures, and thermal stability. The present data on collagens from the marine squid, could help the future endeavors to unwind the therapeutically significant, more secure collagens from marine squid for their utilization in biomedical field.